Recent Publications (Quarterly Journal of Economics, 1958)
Recent Publications Get access The Quarterly Journal of Economics, Volume 72, Issue 1, February 1958, Pages 153–155, https://doi.org/10.1093/qje/72.1.153 Published: 01 February 1958